Analysis of Financial Statements That Act as a Profit Planning Tool at PT. Core of Jaya Perkasa's Work - Muhammad Syamsudin Al Ghifari; Muhamad Imam Syairozi; Abid Muhtarom (Sean Institute, 2025)
One of the plans made by management is profit planning. A tool that is often used to find out financial performance is financial statements. This research aims to assess the company's performance, determine the level of liquidity ratio, solvency, activity and profitability as well as the financial condition of PT. Inti Karya Jaya Perkasa for three years. The method used in this study is quantitative Descriptive. The data collection techniques carried out by the author are documentation and literature review. The data of this research is sourced from the financial statements of PT. The essence of Jaya Perkasa's work. The growth of the company's profits is the main indicator that is important to assess the company's future prospects. The company's financial statements are effective as a profit planning tool. The role of the profitability ratio is very important, judging from the results of the profitability ratio analysis, the Net profit margin ratio analysis, the company's net profit is in good condition. The financial statements of PT. Inti Karya Jaya Perkasa has an effect on profit planning.